Kenya eTrade Readiness Assessment - United Nations Conference on Trade; Development (United Nations, 2022)
The Kenya eTrade Readiness Assessment is the fifth assessment conducted by UNCTAD in a non-LDC country and follows an enhanced methodology. As per this methodology, surveys were disseminated as part of the data collection effort. In Kenya, they targeted respondents in three distinct groups, i.e., public sector, private sector and consumers. Through collaboration with the British Standards Institutions (BSI), an eTrade for All partner, the surveys were enriched to investigate the role of standards in e-commerce development. The assessment adds to the 29 assessments conducted by UNCTAD since 2017. Kenya’s eTrade Readiness Assessment was conducted during a period when the COVID-19 pandemic was ongoing, and it is reflected in some of the findings of the report. The enduring economic and social impacts of the pandemic make it even more important for policy makers and other stakeholders to join forces to take actions aimed at addressing the e-commerce situations. With the eTrade for all partners, UNCTAD is committed to supporting Kenya in its resolve to harness the potential of e-commerce for development.